Noble Gas and Helium Isotope Measurements of Seawater from the Amundsen Sea (Antarctica) - Loose, Brice (IEDA: EarthChem Library, 2018)
Abstract: This dataset contains noble gas and helium isotope measurements of seawater samples collected in the vicinity of the Amundsen Sea, along the coast of Antarctica during the Ocean2ice cruise aboard the RRS James Clark Ross in the 2013/2014 Antarctic Summer.